TRP channels in mammalian hearing loss - Zhang, Zhidong; Wang, Baoshan (Frontiers in Molecular Neuroscience, 2025)
Hearing loss, a common sensory disorder, significantly diminishes quality of life and can stem from diverse causes, including genetic predispositions, aging, noise exposure, and ototoxic medications. Recent research has highlighted the involvement of transient receptor potential (TRP) channels in auditory function and hearing loss. This review offers a comprehensive overview of the current knowledge regarding the roles of TRP channels in mammalian auditory function and hearing loss. By synthesizing the latest research findings, this review aims to elucidate the complex interplay between TRP channels and auditory function, emphasizing their significance in the pathogenesis of hearing loss and identifying potential targets for future therapeutic interventions.